2004
DOI: 10.1590/s1516-35982004000200030
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da gordura de cobertura ao abate, por ultra-som, em tourinhos Brangus e Nelore

Abstract: O objetivo deste trabalho foi verificar a viabilidade da utilização da ultra-sonografia para estimar a espessura de gordura na carcaça (EGSC) no momento do abate. Foram confinados 24 machos inteiros Brangus e 24 Nelore com dietas contendo 20, 40, 60 ou 80% de concentrado. A área de olho de lombo (AOLU) e a espessura de gordura (EGSU) entre a 12ª e a 13ª costelas e a espessura de gordura sobre o músculo Biceps femoris (EGPU), foram obtidas com equipamento de ultra-som PieMedical Scanner 200 Vet com transdutor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
2
0
6
Order By: Relevance
“…Among the factors consid-ered significant in the statistical model, the BT measured on the Longissimus dorsi muscle was an effective indicator of carcass finish in the present study and was inversely correlated with the percentage of retail cuts (Silva et al, 2004). The combined influence of these genotypes on environmental conditions and other genes (associated with carcass traits) might determine the factors related to meat quality.…”
Section: Association Analysismentioning
confidence: 54%
“…Among the factors consid-ered significant in the statistical model, the BT measured on the Longissimus dorsi muscle was an effective indicator of carcass finish in the present study and was inversely correlated with the percentage of retail cuts (Silva et al, 2004). The combined influence of these genotypes on environmental conditions and other genes (associated with carcass traits) might determine the factors related to meat quality.…”
Section: Association Analysismentioning
confidence: 54%
“…The heritability value of WBSF in this study was similar to that found by Elzo et al (1998), who found heritability of 0.17 for WBSF in Brahman animals and crosses. Smith et al (2007) reported higher heritability values for WBSF in Brahman cattle, obtaining estimates around 0.29. Clearly the heritability for meat tenderness can present substantial variation even among animals of the same breed.…”
Section: Resultsmentioning
confidence: 91%
“…Delfa et al (1999) obtiveram correlação de 0,74 entre a avaliação in vivo por ultrassom e na carcaça de cabritos para a espessura de gordura subcutânea determinada entre a 1 a e 2 a vértebra lombar. Silva et al (2004) constataram baixa correlação entre a espessura de gordura subcutânea determinada por ultrassom e na carcaça no início do confinamento de bovinos, e descreveram que o fato pode ser explicado pelo grande número de animais com pouca gordura de cobertura no momento da primeira avaliação da medida com o ultrassom. Portanto, quanto maior a espessura de gordura subcutânea do animal, mais fácil a mensuração da medida e menores as probabilidades de erro.…”
Section: Resultsunclassified